Heritability estimation and environmental factors affecting production traits of Indonesian Ongole cross - Hartati, .; Muladno, .; Jakaria, .; Priyanto, R.; Gunawan, A.; Aryogi, .; Talib, Chalid (Indonesian Animal Sciences Society, 2015)
Productivity data from 560 head of PO cattle have been collected for 9 years from 2004 until 2013 for evaluating heritability estimation and environmental factors affecting production traits of Indonesian Ongole cross from birth to yearling old. Heritability estimation were analyzed using varians analysis with data of paternal halfsib correlation. Varians component for to estimate of heritability value were analyzed using completely randomized design one - way classification. While a general linear model was used to analyze the environmental factors (sex, year, parity, season and type of births). The results showed that sex of calves and year of births had significant differences (P<0.05) for all production traits such as weight at birth, weaning and yearling, while the type of birth only presented a significant difference on birth weight. Parity, season and generation exhibited nonsignificantly effect on those production traits. Estimation of heritability on birth weight, weaning weight and yearling weight were 0.28+0.12; 0.47+0.15 and 0.63+0.17 respectively. The highest heritability values obtained in yearling weight, this means that yearling weight will be effective as selection criteria to improve the genetic of PO cattle. Key Words: Genetic, Non Genetic, Production, PO Cattle